Functional Limitations and Disability in Persons Living with HIV in South Africa and United States: Similarities and Differences. (20th May 2019) - Kietrys, David; Myezwa, Hellen; Galantino, Mary Lou; Parrott, James Scott; Davis, Tracy; Levin, Todd; O'Brien, Kelly; Hanass-Hancock, Jill
Persons living with HIV (PLHIV) may experience disability. We compared disability among PLHIV in the United States and South Africa and investigated associations with health and demographic characteristics. Secondary analysis of cross-sectional data using medical records and questionnaires including the World Health Organization Disability Assessment Schedule (WHO-DAS) 2.0 12-item version (range: 0-36, with higher scores indicative of more severe disability). Between-country differences for the presence of disability were assessed with logistic regression and differences in severity using multiple regression. Eighty-six percent of US participants reported disability, compared to 51.3% in South Africa. The mean WHO-DAS score was higher in the United States (12.09 ± 6.96) compared to South Africa (8.3 ± 6.27). Participants with muscle pain, depression, or more years since HIV diagnosis were more likely to report disability. Being female or depressed was associated with more severity. Being adherent to anti-retroviral therapy (ART) and employed were associated with less severity. Because muscle pain and depression were predictive factors for disability, treatment of those problems may help mitigate disability in PLHIV.